Ostracism, Emotional Labor, Nurse-Patient Relationship and Turnover Intention: A Model of Workplace Ostracism and Its Consequence in Nursing Professional - Li, G.; Ma, S. (13th European Academy of Occupational Health Psychology Conference, 2018)
Ostracism, Emotional Labor, Nurse-Patient Relationship and Turnover Intention: A Model of Workplace Ostracism and Its Consequence in Nursing Professional Although the bulk of the research suggests that workplace ostracism negatively affects one’s psychological emotions and attitudes, limited research has addressed how such psychological impact leads to work-related behavioral outcomes. Drawing on emotional regulation and conservation of resources theory, we argue that when one perceives ostracism, that individual may deliberately regulate their emotions by engaging emotional labor (typically with surface acting or deep acting) which impacts job performance and further leads to turnover intention. This study employed a time-lagged survey design with 379 staff nurses from one large public hospital in China. Participants completed a survey at two points in time with measures of the major study variables in the hypothesized model. Structural equation modeling was used to test the relationship between workplace ostracism and turnover intention via emotional labor (surface acting vs deep acting) and nurse-patient relationship. Findings provided support for the hypothesized model differentially linking workplace ostracism, deep acting /surface acting, nurse-patient relationship, and turnover intention. Specifically, 1) the path from workplace ostracism to surface acting shows a significant positive coefficient, just as well as the path to deep acting; 2) while the path from surface acting to nurse-patient relationship shows a significant coefficient, there is an absence of relation between deep acting and nurse-patient relationship; 3) lastly nurse-patient relationship had a significant negative direct effect on turnover intention. Overall, the results suggest that only surface acting as an emotional labor regulation strategy mediates the negative relationship between workplace ostracism and patient care (nurse-patient relationship), which negatively influence turnover intention. Our study contributes to the literature in the following ways. First of all, this study introduces emotional labor in the process of workplace ostracism and its consequences, which better explains how workplace ostracism impacts employee behavior and work-related outcome. By so doing, we integrate the psychological impact and pragmatic impact of ostracism in Robinson, O’Reilly and Wang’s model (2013). In our study, the impacts’ pathway is sequential rather than parallel as Robinson et al. proposed (2013). Second, this study narrows our knowledge gap about the relationship between workplace ostracism and turnover intention with empirical support from a nurse sample in an under-researched setting – Chinese public hospital. The practical value of this study lies in the implication for hospital managers to better manage nurses for nursing care quality and nurse retention.